Comparison of retinal sensitivity between professional soccer players and non-athletes - Pereira, V. B. P.; Pereira, V. B. P.; Pereira, R. A.; Kasahara, N. (International Journal of Sports Medicine, 2016)
The purpose of the study was to compare the peripheral retinal sensitivity of the visual field between professional soccer players and age-gender matched non-athlete subjects. All participants underwent a complete eye evaluation. The visual field was evaluated with the achromatic program 60-4 from the Humphrey automated perimetry. The binocular visual field was created with the best location model. It was divided into 4 quadrants (left superior, right superior, left inferior, and right inferior) and compared between groups. The study group comprised 29 professional male football players and the control group comprised 26 age-matched male non-athletes. Mean age was 25.8±4.7 years in the study group and 26.3±5.1 for controls. The average of retina sensitivity in the left inferior and right inferior quadrants was higher in the study group (27.2±1.2 dB and 27.0±1.4 dB) as compared to controls (26.1±1.9 dB and 25.5±2.1 dB). (Student`s t test, P=0.011 and P=0.004, respectively). In this small cohort, professional soccer players presented higher retina sensitivity in the inferior quadrants when compared to non-athletes.